Ever decreasing circles: how changing global music industry strategies impact film composers working in audiovisual industries in Ireland - Rogers, Jim (Irish Journal of Arts Management and Cultural Policy, 2024)
This article examines the unfolding relationship between ‘global’ music labels and the ‘local’ audio-visual sector in the context of a changing music industry landscape. In recent years, major transnational music labels have increasingly pursued activities in local audiovisual production spaces. This reflects the evolving form and nature of these companies as they find new and more diverse ways to generate revenue and maximise their returns on the recording and music publishing rights and brands under their control. These labels have been adapting to the challenges and opportunities afforded by a rapidly evolving digital context, and, as such, have been redirecting resources to develop new, or intensify existing interests in areas beyond the direct sale or licensing of music to consumers and platforms. In this article, we are interested in a number of key developments that hold specific implications for the ‘local’ audiovisual domain. These relate to the approach taken by these labels to synchronisation rights, as well as their involvement in delivering production music libraries and bespoke composition to film, television and advertising production. The nature of the developments outlined below illustrates how recording and music publishing companies have evolved closer relationships with local audiovisual producers. While blanket music licensing agreements provide small, independent film and television production companies with access to song catalogues and music libraries that would once have been beyond their budgetary limits, the nature of such licensing arrangements carries potentially harmful implications for local film composers and those involved in (music) post-production.